Solid-state compounds of 4-methoxybenzylidenepyruvate and cinnamylidenepyruvates with thorium (IV) - Preparation and thermal studies - Schnitzler, E.; Melios, C. B.; Ionashiro, Massao [UNESP] (Kluwer Academic Publ, 2002)
By close control of experimental variables affecting precipitation, solid-state compounds of the type Th(OH)(m)L4-m.nH(2)O, where L stands for 4-methoxy-benzylidenepyruvate, cinnamylidenepyruvate or 4-dimethylaminocinnamylidene-pyruvate; m=0 to 3 and n=0.5-3 were isolated. Chemical analysis, TG, DTG, DSC and X-ray powder diffractometry have been employed to characterize and to study the thermal behavior of these compounds in dynamic air atmosphere. In all cases, hydration water is slowly lost between 30 and 160degreesC; a continuous, slow rate, mass loss is observed thereafter and beyond 280-400degreesC the rate of decomposition/oxidation increased rapidly, to give ThO2 as the final product, beginning at 412-510degreesC. The results associated with the hydroxo-compounds indicate that the loss of constitution water (OH ions) and the decomposition / oxidation of the organic moieties occur as simultaneous process.
Keywords: cinnamylidenepyruvates; 4-methoxybenzylidenepyruvate; thermal decomposition; Th(IV) compounds